Exploration on Mechanical Behaviours of Hyacinth Fibre Particles Reinforced Polymer Matrix-Based Hybrid Composites for Electronic Applications. (6th December 2021) - Kumar Panda, Pradeep; Jebastine, J.; Ramarao, Madhialagan; Fairooz, Shaik; Reddy, Chirra Kesava; Nasif, Omaima; Alfarraj, Saleh; Manikandan, Velu; Jenish, I.
Abstract : Biocomposites with polylactic acid (PLA), nanosilica parts, and water hyacinth fibres have been developed in this experimental study. By changing the weight percentage of nanosilica particulate matter (0, 2, 4, 6, and 8 percent) with PLA and water hyacinth fibres, five composite mates were produced through a double screw extruder and compression moulding machine. According to the ASTM standards, the process to machine, the composite specimens have been adopted from the water jet machining process. The tensile, compression, flexural, impact, hardness, and water absorption tests were performed on the composite specimens to assess various mechanical properties and absorbance behaviour. The test findings reveal the significant improvement in the tensile and flexural properties of the composites. Composites contain 6 percent of the fine nanosilica particles by weight. Concerning adding the growing weight percentage (4 percent) of nanosilica particles to the composites, the water absorption properties of the composites have significantly improved. The tensile strength of 6% nanosilica mixed specimens showed the highest tensile stress rate as 36.93 MPa; the value was nearly 3.5% higher than the 4% nanosilica mixed composite specimens.